Radiation-resistant medium-entropy ceramic material as well as preparation method and application thereof

By preparing the radiation-resistant medium-entropy ceramic material (TiaZrbNbc)C, the problem of insufficient performance of nuclear fuel cladding materials under high irradiation environment was solved, achieving low neutron absorption cross section and good radiation resistance, making it suitable for cladding materials of fourth-generation reactors.

CN120923235APending Publication Date: 2025-11-11SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410570315.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-09
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing nuclear fuel cladding materials face harsh environments such as high radiation, corrosion, and abrasion under high temperature and pressure, resulting in insufficient radiation resistance and limiting the safety and development of nuclear energy.

Method used

By using radiation-resistant medium-entropy ceramic material (TiaZrbNbc)C, the composition of Zr and Nb was increased through non-equimolar ratio design, and combined with carbothermal reduction and hot pressing sintering processes, a ceramic material with low neutron absorption cross section and good radiation resistance was prepared.

Benefits of technology

Under high irradiation conditions, medium-entropy ceramic materials exhibit low irradiation swelling and small helium bubbles, and possess excellent radiation resistance and high-temperature mechanical properties, making them suitable for cladding materials in fourth-generation reactors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120923235A_ABST
    Figure CN120923235A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nuclear reactor materials, and particularly relates to anti-radiation medium-entropy ceramic as well as a preparation method and application thereof. In order to enable a core material of a fourth-generation reactor to have better radiation resistance, the invention provides the radiation-resistant medium-entropy ceramic material, and the chemical composition of the radiation-resistant medium-entropy ceramic material is (TiaZrbNbc) C, wherein a is equal to 5at%-33at%, b is equal to 33-67at%, c is equal to 33at%-58at%, a + b + c is equal to 1, and the component of Zr and Nb is higher than that of Ti. The components of transition metals (Ti, Zr and Nb) are regulated and controlled, and the components of Zr and Nb are higher than those of Ti, so that the medium-entropy ceramic still has a low neutron absorption cross section.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a radiation-resistant intermediate-entropy ceramic, its preparation method, and its application, belonging to the field of nuclear reactor materials technology. Background Technology

[0002] Nuclear energy, as an important component of clean energy, has advantages over fossil fuels, such as high efficiency, cleanliness, and abundant reserves.

[0003] However, the safety of nuclear energy is a major factor limiting its development. The nuclear fuel cladding tube is one of the most critical components in the reactor core structure, operating in the most demanding environment. It not only comes into direct contact with the nuclear fuel but also with the coolant under high temperature and pressure, facing harsh conditions such as high temperature, strong radiation, strong corrosion, and high abrasion. Therefore, developing cladding materials with better performance is a crucial guarantee for nuclear energy safety. Summary of the Invention

[0004] The purpose of this invention is to provide a radiation-resistant intermediate-entropy ceramic, its preparation method, and its application, so as to enable the core material of fourth-generation reactors to have better radiation resistance.

[0005] In a first aspect, the present invention provides a radiation-resistant intermediate-entropy ceramic material, wherein the chemical composition of the radiation-resistant intermediate-entropy ceramic material is (Ti a Zr b Nb c C; wherein a = 5 at%–33 at% , b = 33–67 at% , c = 33 at%–58 at% , a + b + c = 1 , and the Zr and Nb compositions are higher than Ti (i.e., b > a, c > a). Preferably, a = 5 at%–25 at% , b = 35–55 at% , c = 35 at%–40 at%. Even more preferably, a = 15 at%–25 at% , b = 40–45 at% , c = 35 at%–40 at%.

[0006] Considering the requirement for cladding materials to have a low neutron absorption cross-section, the inventors creatively employed a non-equimolar ratio design to increase the Zr content. This allows the radiation-resistant medium-entropy ceramic material to achieve a lower neutron absorption cross-section while maintaining superior high-temperature performance and radiation resistance. The radiation-resistant medium-entropy ceramic of this invention exhibits good radiation resistance, high-temperature resistance, and a small neutron absorption cross-section, making it suitable for use as cladding material in fourth-generation fission reactor nuclear energy systems. Radiation resistance experiments revealed that, under the same irradiation conditions, it produces smaller helium bubbles than unary zirconium carbide ceramics, indicating that this medium-entropy ceramic material possesses excellent radiation resistance.

[0007] Preferably, at room temperature and with an irradiation damage dose of 2.5 dPa, the irradiation swelling of the radiation-resistant intermediate-entropy ceramic material is ≤0.6%. The neutron absorption cross section of the radiation-resistant medium-entropy ceramic material shall not exceed 2.7b, preferably not exceed 2.1b; The average size of the helium bubbles produced by the radiation-resistant medium-entropy ceramic material after annealing at 1500℃ does not exceed 3.5nm.

[0008] Secondly, the present invention provides a method for preparing a radiation-resistant intermediate-entropy ceramic material, comprising: (1) According to the chemical composition of radiation-resistant medium-entropy ceramic materials (Ti a Zr b Nb c Weigh TiO2 powder, ZrO2 powder, Nb2O5 powder and graphite as raw materials and mix them to obtain a powder mixture; (2) The resulting powder mixture was subjected to a carbothermic reduction reaction to obtain carbide powder; (3) The carbide powder is placed in a graphite mold and sintered by hot pressing to obtain the radiation-resistant intermediate entropy ceramic material.

[0009] Preferably, in step (1), the mixing method is wet ball milling; the parameters of the wet ball milling include: ethanol as the milling medium, zirconia balls as the milling balls, a rotation speed of 400-500 rpm, and a time of 24-48 hours.

[0010] Furthermore, preferably, after wet ball milling and mixing, the ethanol is removed by rotary evaporation, and finally the mixture is sieved; the sieve mesh size is 200 mesh.

[0011] Preferably, in step (2), the parameters of the carbothermic reduction reaction include: vacuum degree controlled below 10 Pa, temperature controlled at 1600℃~1700℃, and reaction time of 0.5~1.5h.

[0012] In step (3), the carbide powder is crushed and sieved through a 200-mesh sieve and then placed into a graphite mold.

[0013] Preferably, in step (3), the parameters of the hot pressing sintering include: high-purity argon gas as a flowing inert atmosphere, uniaxial pressure of 20-50 MPa, temperature of 2100-2200℃; heat holding and pressure holding time of 1-2 hours; preferably, the purity of the high-purity argon gas is greater than 99.9%.

[0014] Thirdly, the present invention provides an application of the above-mentioned radiation-resistant intermediate-entropy ceramic material in key components of nuclear power plant cores or fuel cladding materials within nuclear power plant reactors.

[0015] Beneficial effects: The radiation-resistant medium-entropy ceramic of this invention exhibits excellent radiation resistance and can be applied to fourth-generation reactor cladding materials. By introducing multiple transition metal components to increase the entropy of the ceramic material, its stability is improved. Furthermore, the lattice distortion, atomic dispersion, and valence state compensation brought about by medium entropy further enhance radiation resistance. By controlling the composition of each transition metal (Ti, Zr, Nb), with Zr and Nb components being higher than Ti, the medium-entropy ceramic still maintains a low neutron absorption cross section. Radiation resistance experiments on the ceramic material show that, compared to traditional zirconium carbide ceramics, this radiation-resistant medium-entropy ceramic has better resistance to radiation swelling, and after heat treatment, the helium bubbles generated by irradiation are smaller and the dislocations are shorter. Attached Figure Description

[0016] Figure 1 For example, (Ti) in Example 2 0.33 Zr 0.34 Nb 0.33 XRD pattern of C; Figure 2 In Example 4 (Ti) 0.33 Zr 0.34 Nb 0.33 Comparison of helium bubble distribution in grains of medium-entropy ZrC ceramics and unary ZrC ceramics after helium ion irradiation at 540 keV and heat treatment at 1500℃. Detailed Implementation

[0017] The present invention will be further illustrated by the following embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the present invention.

[0018] In this field, the concept of medium entropy offers opportunities for designing radiation-resistant materials at the nanoscale and atomic scale. Studies have shown that medium entropy alloys maintain relatively high phase stability, good anti-expansion properties, and inhibit helium bubble formation at very high radiation doses at room temperature. Unlike metallic bonds in alloys, ceramics contain covalent, ionic, and metallic bonds. Carbide ceramics, with their high melting points, excellent high-temperature mechanical properties, and low neutron absorption cross sections, are promising candidate structural materials for next-generation nuclear reactors. The inventors have creatively discovered that medium entropy carbide ceramics exhibit even superior radiation resistance.

[0019] Based on this, the present invention combines the advantages of medium-entropy ceramics and traditional nuclear power materials, so that the resulting medium-entropy ceramics have excellent comprehensive performance, namely, low neutron absorption cross section, good high-temperature mechanical properties, radiation resistance and corrosion resistance.

[0020] Specifically, the radiation-resistant medium-entropy ceramic material in this invention is composed of titanium, zirconium, niobium, and carbon, and the medium-entropy ceramic composition is designed according to a non-equimolar ratio as follows: (Ti a Zr b Nb cC(a+b+c=1). The transition metal elements Zr and Nb in this radiation-resistant intermediate-entropy ceramic are higher than those in Ti, where a=5at%~33at%, b=33~67at%, and c=33at%~58at%. Ta and W are not added in this invention, which can reduce the overall neutron absorption cross section of the material (an important indicator of core materials).

[0021] The following is an exemplary description of a method for preparing radiation-resistant intermediate-entropy ceramics.

[0022] Mixing. Powdered TiO2, ZrO2, Nb2O5 and graphite are mixed in ethanol in a certain molar ratio of transition metals and graphite in a corresponding proportion. All these raw materials are commercial powders with a purity greater than 99.9% to ensure that the composition of the medium-entropy ceramic powder obtained by the carbothermal reduction reaction of the raw materials meets the design requirements.

[0023] Ball milling and sieving. The mixed powder was ball milled with ZrO2 ball media for 24 hours, and the ethanol was removed by a rotary evaporator under vacuum at 60°C. The resulting mixture was dried and then sieved through a 200-mesh sieve.

[0024] Carbide powder was obtained by carbothermic reduction reaction. The sieved powder mixture was reacted at 1600℃-1700℃ for 0.5-1.5h under a vacuum of less than 10Pa.

[0025] Hot pressing. The carbide powder is sieved through a 200-mesh sieve, placed in a graphite mold, and held at 2000-2200℃ for 1-2 hours under uniaxial pressure of 20-50MPa and flowing argon gas (purity >99.9%).

[0026] Performance testing: The ceramic irradiation process involves: first, polishing the bulk ceramic, then subjecting it to 540 keV He irradiation at room temperature. 2+ Ion beam irradiation, with a cumulative ion flux of 1×10 17 / cm 2 .

[0027] By subjecting irradiated medium-entropy ceramics to a heat treatment at 1500℃, the operating conditions of a nuclear reactor accident can be simulated, and the defects generated by irradiation (such as dislocations and helium bubbles) can be observed more clearly.

[0028] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values ​​in the examples below.

[0029] Example 1: (1) Mixing: Commercial powders of TiO2, ZrO2, Nb2O5 and graphite with a purity greater than 99.9% were mixed in ethanol at a molar ratio of 0.15:0.45:0.2:2.3; (2) Ball milling and sieving: The mixed powder was ball milled with ZrO2 ball media for 24 hours, and the ethanol was removed by a rotary evaporator under vacuum at 60°C. The resulting mixture was dried and then sieved through a 200-mesh sieve. (3) Carbide powder is obtained by carbothermic reduction reaction: The sieved powder mixture is reacted at 1600℃ for 1.5h under a vacuum of less than 10Pa; (4) Hot pressing: The carbide powder that has passed through a 200-mesh sieve is placed into a graphite mold and hot-pressed for 1 hour at 2200℃ under a uniaxial pressure of 20MPa and under flowing argon gas (purity > 99.9%).

[0030] Radiation resistance tests were conducted on the ceramic material obtained in Example 1. The test results showed that the medium-entropy ceramic, at room temperature, with a radiation damage dose of approximately 2.5 dPa, (Ti 0.15 Zr 0.45 Nb 0.4 The irradiation swelling of Ti (0.5%) was lower than that of traditional ZrC ceramics (1%), indicating that its resistance to radiation damage is superior to that of traditional ZrC ceramics. The obtained (Ti) 0.15 Zr 0.45 Nb 0.4 The neutron absorption cross section of C is approximately 1.458 μb, which is lower than that of Ti. 0.33 Zr 0.34 Nb 0.33 )C of 2.478b.

[0031] Example 2: (1) Mixing: Commercial powders of TiO2, ZrO2, Nb2O5 and graphite with a purity greater than 99.9% were mixed in ethanol at a molar ratio of 0.25:0.4:0.175:3.175; (2) Ball milling and sieving: The mixed powder was ball milled with ZrO2 ball media for 48 hours, and then evaporated at 60°C using a rotary evaporator. (3) Remove ethanol under vacuum, dry the resulting mixture, and then sieve the powder mixture through a 200-mesh sieve. (4) Carbide powder is obtained by carbothermic reduction reaction: The sieved powder mixture is reacted at 1700℃ for 0.5h under a vacuum of less than 10Pa; (5) Hot pressing: The sieved carbide powder is placed in a graphite mold and hot-pressed at 2000℃ for 2 hours under a uniaxial pressure of 50MPa and under flowing argon gas (purity > 99.9%).

[0032] like Figure 1 The image shows the XRD pattern of this radiation-resistant medium-entropy ceramic. The pattern reveals that the ceramic exhibits an FCC structure. Studies have shown that the FCC structure demonstrates superior radiation resistance compared to the HCP structure, giving this medium-entropy ceramic excellent radiation resistance and making it a potential material for nuclear power plant structures. The obtained (Ti) 0.25 Zr 0.4 Nb 0.35 The neutron absorption cross section of C is approximately 2.001 lb, which is lower than that of Ti. 0.33 Zr 0.34 Nb 0.33 )C of 2.478b.

[0033] Example 3: Radiation resistance tests were conducted on the ceramic material obtained in Example 2. The test results showed that, at room temperature, the ZrC ceramic and (Ti) ceramic were subjected to radiation damage doses of approximately 2.5 dPa. 0.25 Zr 0.4 Nb 0.35 The material structure of medium-entropy ceramics (Ti) remains unchanged, and the material structure of medium-entropy ceramics (Ti) remains unchanged. 0.25 Zr 0.4 Nb 0.35 The radiation swelling resistance of ZrC (0.6%) is better than that of traditional ceramic ZrC (1%).

[0034] Example 4: The irradiated sample from Example 3 was annealed at 1500℃ to obtain a medium-entropy ceramic (Ti). 0.25 Zr 0.4 Nb 0.35 The average size of the helium bubbles produced by ZrC (2.3 nm) is smaller than that of conventional ceramic ZrC (5.5 nm), such as... Figure 2 As shown, the dislocations are shorter, indicating that the medium-entropy material has good radiation resistance.

[0035] Example 5: The preparation process of the radiation-resistant intermediate-entropy ceramic material in Example 5 is the same as in Example 1, the only difference being: the chemical formula (Ti) 0.05 Zr 0.55 Nb0.4 C. Performance testing is described in Example 1.

[0036] Example 6: The preparation process of the radiation-resistant intermediate-entropy ceramic material in Example 6 is the same as in Example 1, the only difference being: the chemical formula (Ti 0.10 Zr 0.50 Nb 0.4 C. Performance testing is described in Example 1.

[0037] Example 7: The preparation process of the radiation-resistant intermediate-entropy ceramic material in Example 7 is the same as in Example 1, with the only difference being: the chemical formula (Ti) 0.20 Zr 0.40 Nb 0.4 C. Performance testing is described in Example 1.

[0038] Example 8: The preparation process of the radiation-resistant intermediate-entropy ceramic material in Example 8 is the same as in Example 1, with the only difference being: the chemical formula (Ti) 0.25 Zr 0.35 Nb 0.4 C. Performance testing is described in Example 1.

[0039] Comparative Example 1 The traditional preparation process of ZrC ceramics includes: (1) Mixing: Commercial powder ZrO2 with a purity greater than 99.9% and graphite are mixed in ethanol at a molar ratio of 1:3; (2) Ball milling and sieving: The mixed powder was ball milled with ZrO2 ball media for 48 hours, and the ethanol was removed by a rotary evaporator under vacuum at 60°C. The resulting mixture was dried and then sieved through a 200-mesh sieve. (3) Carbide powder is obtained by carbothermic reduction reaction: The sieved powder mixture is reacted at 1700℃ for 0.5h under a vacuum of less than 10Pa; (4) Hot pressing: The sieved carbide powder is placed in a graphite mold and hot-pressed at 2100℃ for 1 hour under a uniaxial pressure of 30MPa and under flowing argon gas (purity > 99.9%).

[0040] Comparative Example 2 The preparation process of the radiation-resistant intermediate-entropy ceramic material in Comparative Example 2 is the same as in Example 1, the only difference being the chemical formula (Ti 0.33 Zr 0.34 Nb 0.33 C. Performance testing is described in Example 1.

[0041] Table 1: Chemical formula helium bubble size Anti-radiation swelling ability Neutron absorption cross section Example 1 <![CDATA[(Ti 0.15 Zr 0.45 Nb 0.4 )C]]> 3.0nm 0.5% 1.458b Example 2 <![CDATA[(Ti 0.25 Zr 0.4 Nb 0.35 )]]> - - 2.001b Example 3 <![CDATA[(Ti 0.25 Zr 0.4 Nb 0.35 )C]]> - 0.6% - Example 4 <![CDATA[(Ti 0.25 Zr 0.4 Nb 0.35 )C]]> 2.3nm - - Example 5 <![CDATA[(Ti 0.05 Zr 0.55 Nb 0.4 )C]]> 3.5nm 0.45% 0.866b Example 6 <![CDATA[(Ti 0.10 Zr 0.50 Nb 0.4 )C]]> 3.3nm 0.48% 1.162b Example 7 <![CDATA[(Ti 0.20 Zr 0.40 Nb 0.4 )C]]> 2.8nm 0.53% 1.754b Example 8 <![CDATA[(Ti 0.25 Zr 0.35 Nb 0.4 )C]]> 2.5nm 0.57% 2.049b Comparative Example 1 ZrC 5.5nm 1% 0.184b Comparative Example 2 <![CDATA[(Ti 0.33 Zr 0.34 Nb 0.33 )C]]> 2.6nm 0.55% 2.478b 。

Claims

1. A radiation-resistant intermediate-entropy ceramic material, characterized in that, The chemical composition of the radiation-resistant medium-entropy ceramic material is (Ti a Zr b Nb c C; where a = 5at%~33at%, b = 33~67at%, c = 33at%~58at%, a+b+c = 1, and the composition of Zr and Nb is higher than that of Ti.

2. The radiation-resistant intermediate-entropy ceramic material according to claim 1, characterized in that, a=5at%~25at%, b=35~55at%, c=35at%~40at%.

3. The radiation-resistant intermediate-entropy ceramic material according to claim 1 or 2, characterized in that, At room temperature, with an irradiation damage dose of 2.5 dPa, the irradiation swelling of the radiation-resistant intermediate-entropy ceramic material is ≤0.6%. The neutron absorption cross section of the radiation-resistant medium-entropy ceramic material does not exceed 2.7b; The average size of the helium bubbles produced by the radiation-resistant medium-entropy ceramic material after annealing at 1500℃ does not exceed 3.5nm.

4. A method for preparing a radiation-resistant intermediate-entropy ceramic material according to any one of claims 1-3, characterized in that, include: (1) Weigh TiO2 powder, ZrO2 powder, Nb2O5 powder and graphite as raw materials and mix them to obtain a powder mixture; (2) The resulting powder mixture was subjected to a carbothermic reduction reaction to obtain carbide powder; (3) The carbide powder is placed in a graphite mold and sintered by hot pressing to obtain the radiation-resistant intermediate entropy ceramic material.

5. The preparation method according to claim 4, characterized in that, In step (1), the mixing method is wet ball milling; the parameters of the wet ball milling include: ethanol as the milling medium; zirconia balls as the milling balls; rotation speed of 400-500 rpm; and time of 24-48 hours.

6. The preparation method according to claim 5, characterized in that, After wet ball milling and mixing, ethanol is removed by rotary evaporation, and finally the mixture is sieved; the sieve mesh size is 200 mesh.

7. The preparation method according to any one of claims 4-6, characterized in that, In step (2), the parameters of the carbothermic reduction reaction include: vacuum degree controlled below 10 Pa, temperature controlled between 1600℃ and 1700℃, and reaction time between 0.5 and 1.5 h.

8. The preparation method according to any one of claims 4-7, characterized in that, In step (3), the carbide powder is first crushed and sieved through a 200-mesh sieve and then placed into a graphite mold.

9. The preparation method according to any one of claims 4-8, characterized in that, In step (3), the parameters of the hot pressing sintering include: high-purity argon gas as a flowing inert atmosphere, uniaxial pressure of 20-50 MPa, temperature of 2100-2200℃; heat holding and pressure holding time of 1-2 hours; preferably, the purity of the high-purity argon gas is greater than 99.9%.

10. The application of any one of the radiation-resistant intermediate-entropy ceramic materials according to claims 1-3 in key components of a nuclear power plant core or in fuel cladding materials within a nuclear power plant reactor.